Amygdalar activity among patients with head and neck cancer predicts cerebrovascular events: a retrospective FDG PET/CT Cohort Study. (25th November 2020) - Hassan, M; Abohashem, S; Wang, Y; Jones O'connor, M; Alvi, R.M; Zlotoff, D.A; Bakar, R.B; Osborne, M.T; Chan, A.W; Wirth, L.J; Awadalla, M.A; Addison, D; et al.
Abstract: Background: Radiation therapy for head and neck cancer (HNC) associates with an increase in cerebrovascular events. Amygdalar metabolic activity (AmygA), a measure of stress-associated neurobiological activity, associates with cardiovascular events in patients without cancer. In this study, we tested whether AmygA was associated with cerebrovascular events among patients treated with radiation therapy. Methods: The associations between AmygA (at cancer staging) and subsequent cerebrovascular events as well as inflammatory biomarkers and arterial inflammation, were tested among consecutive patients with HNC treated with radiation therapy who underwent 18F-FDG-PET/CT. Results: Among 240 patients (59±13 years; 30% female, 48% had stage 4 disease), there were 26 events over a median follow-up period of 3 years (IQR: 1.7–5.1). AmygA at cancer staging was associated with subsequent cerebrovascular events, an effect that remained significant after adjustment for age, sex, and cerebrovascular risk factors (adjusted hazard ratio 1.47, 95% CI 1.04–2.09, P=0.031). The association persisted when the analysis was restricted to patients with no prior history of CV disease and even among those with lower predicted CV risk (P<0.001). Higher AmygA at cancer staging also associated with serum inflammatory markers and arterial inflammation (P<0.05 each). Conclusions: Amygdalar activity, a quantifiable biomarker of stress-associated brain activity, associated with subsequent cerebrovascular events among patients with cancer treated with radiation therapy. Funding Acknowledgement: Type of funding source: None